Excess DHA Induces Liver Injury via Lipid Peroxidation and Gut Microbiota-Derived Lipopolysaccharide in Zebrafish - Ding, Qianwen; Hao, Qiang; Zhang, Qingshuang; Yang, Yalin; Olsen, Rolf Erik; Ringø, Einar; Ran, Chao; Zhang, Zhen; Zhou, Zhigang (Frontiers in Nutrition, 2022)
Being highly unsaturated, n-3 long-chain polyunsaturated fatty acids (LC-PUFAs) are prone to lipid peroxidation. In this study, zebrafish were fed with low fat diet (LFD), high fat diet (HFD) or 2% DHA-supplemented HFD (HFDHA2.0). To study the possible negative effects of high level of dietary DHA, growth rates, blood chemistry, liver histology, hepatic oxidative stress, apoptosis and inflammatory processes were assessed. Cell studies were used to quantify the effects of DHA and antioxidants on cellular oxidative stress and viability. The possible interaction between gut microbiota and zebrafish host was evaluated in vitro. HFDHA2.0 had no effects on hepatic lipid levels but induced liver injury, oxidative stress and hepatocellular apoptosis including intrinsic and death receptor-induced apoptosis. Besides, inclusion of 2 % DHA in HFD increased the abundance of Proteobacteria in gut microbiota and serum endotoxin levels. In the zebrafish liver cell line (ZFL) model, DHA activated intrinsic apoptosis while the antioxidant 4-hydroxy-Tempo (tempo) inhibited the pro-apoptotic negative effects of DHA. The apoptosis induced by lipopolysaccharide (LPS) was unaffected by the addition of tempo. In conclusion, excess DHA supplementation generates hepatocellular apoptosis-related injury to liver. The processes might propagate along at least two routes, involving lipid peroxidation and gut microbiota-generated LPS.